Exploring the Influence of Personality Traits on Learning Satisfaction and Motivation in Online Education - Fitriana, Deva Nur; Maruf, Nirwanto; Asmara, Candra Hadi (Jetlal, 2025)
This study investigates the relationships among the Big Five Personality Traits, online learning satisfaction, and learning motivation in the context of Indonesian secondary education. The objective is to examine how personality traits influence students’ satisfaction and motivation in virtual learning environments, addressing the gap in understanding these dynamics in younger learners. Employing a correlational quantitative research design, the study involved 149 ninth-grade students from an Islamic junior high school in Indonesia. Data were collected using three validated instruments: The Big Five Inventory Questionnaire, Learner Satisfaction Survey, and English Motivation Questionnaire. Pearson Product-Moment correlation analysis was used to determine the relationships among the variables. The findings reveal strong positive correlations between online learning satisfaction and learning motivation (r = 0.955), the Big Five Personality Traits and satisfaction (r = 0.986), and personality traits and motivation (r = 0.950). Conscientiousness, agreeableness, and openness to experience emerged as significant predictors of satisfaction and motivation. These results highlight the importance of creating supportive and adaptive online learning environments tailored to individual differences. However, the study is limited by its single-school setting and reliance on self-reported data. Future research should expand to diverse educational contexts and explore additional moderating factors. This study recommends designing inclusive virtual learning environments that integrate personality-based teaching strategies to enhance engagement and learning outcomes.